Description and systematic affinity of flower and seed fossils of Erica sect. Chlorocodon (Ericaceae) from the early Pleistocene of Madeira Island, Portugal. Issue 2 (15th February 2023) - Góis‐Marques, Carlos A.; de Nascimento, Lea; Fernández‐Palacios, José María; Madeira, José; de Sequeira, Miguel Menezes
Abstract: Palaearctic Erica sect. Chlorocodon, known as the wind‐pollinated besom heaths (WPBH), includes the Macaronesian E. azorica, E. platycodon subsp. platycodon and E. platycodon subsp. maderincola together with the Mediterranean and North African E. scoparia . Despite the broad extant distribution, the mainland fossil record of this section is scarce and poorly preserved and dated, and Macaronesian fossils were so far unknown. Here we discuss the systematic affinities of the first fossils of a WPBH found in Macaronesia, within a 1.3 Ma (Pleistocene, Calabrian stage) Madeira Island fossiliferous deposit. One flower and dissociated seed fossils were found in the same sediment layer, being preserved as coalified compressions with cuticular preservation. Both the flower and seed fossils present unique WPBH characters. The flower fossil is characterised by an exserted, peltate and discoid stigma – an unequivocal adaptation to anemophily, unique within Palaearctic Erica taxa. The seed fossils are of small size, presenting a testa with channelled anticlinal cell‐walls, a characteristic only found in the extant Macaronesian WPBH. Morphological, anatomical, and biometric comparisons of the fossils to extant flowers and seeds suggest that the fossils are related to the Palaearctic E.  sect. Chlorocodon, being morphologically close to E. azorica . Here we assign them to E.  aff. azorica. These findings suggest a colonisation to Madeira Island prior to 1.3 Ma, corresponding to the oldest and unambiguous WPBH fossils, at least 0.90–1.2 Ma older than the oldest known record. The fossil flower also indicates the presence of anemophilous traits since at least the early Pleistocene. Finally, the presence of a WPBH could suggest the same ecological role in seral communities, important to the establishment of the Madeiran temperate stink‐laurel forest.